Characteristics of Half Wave and Full Wave Power Supply Based on Proteus Application Simulation - Sunardi (Piston: Journal of Technical Engineering, 2025)
This study uses a simulation-based approach with the Proteus application to discuss the characteristics of half-wave and full-wave power supplies. Power supplies are essential components in electronic systems that convert AC voltage into DC voltage. In this study, the design and simulation of half-wave and full-wave rectifier circuits were carried out to observe the differences in performance and characteristics of each type, such as DC output voltage value, ripple, and rectification efficiency. The simulation results show that the full-wave power supply produces a more stable DC output voltage with lower ripple compared to the half-wave power supply. Additionally, the rectification efficiency in full-wave circuits is higher because rectification occurs in every AC cycle, while in half-wave circuits it only occurs in half of the cycle. This simulation provides a clear overview of the advantages and disadvantages of each type of power supply, thus serving as a useful reference in the design of power supply systems for various electronic applications.